The Challenge of Reducing International Trade and Migration Barriers - Anderson, Kym; Winters, L. Alan (World Bank, Washington, DC, 2012)
While barriers to trade in most goods and some services including capital flows have been reduced considerably over the past two decades, many remain. Such policies harm most the economies imposing them, but the worst of the merchandise barriers (in agriculture and textiles) are particularly harmful to the world's poorest people, as are barriers to worker migration across borders. This paper focuses on how costly those anti-poor trade policies are, and examines possible strategies to reduce remaining distortions. Two opportunities in particular are addressed: completing the Doha Development Agenda process at the World Trade Organization (WTO), and freeing up the international movement of workers. A review of the economic benefits and adjustment costs associated with these opportunities provides the foundation to undertake benefit/cost analysis required to rank this set of opportunities against those aimed at addressing the world's other key challenges as part of the Copenhagen Consensus project. The paper concludes with key caveats and suggests that taking up these opportunities could generate huge social benefit/cost ratios that are considerably higher than the direct economic ones quantified in this study, even without factoring in their contribution to alleviating several of the other challenges identified by that project, including malnutrition, disease, poor education and air pollution.